Percepção da imagem corporal, hábitos alimentares e consumo de bebidas alcoólicas de ingressantes na universidade - Mota, Gizelle Andrêa Lima (2017)
The concept of healthy and beautiful body is dynamic. The pursuit of a slim, athletic, well defined shaped body is a desired goal specially within teenagers and young adults. Concomitantly, the lifestyle changes has altered the eating patterns and the consumption of ethanol, specially in college freshman during the academic life adaptations and the new social environment. Objective: To analyze the association between the perception of body image with eating habits and average consumption of ethanol among college students. Methods: Cross sectional study conducted with college students between the age of 16 to 25 years old, both genders, enrolled in 21 full time courses of the Federal University of Mato Grosso, Cuiaba-MT campus, first semester 2015. The students responded to a questionnaire to evaluate social-demographic, economic, life style characteristics (eating habits and the consumption of alcohol). It was identified the satisfactory/unsatisfactory of body self-perception using the Stunkard scale that presents a set of nine silhouette for both genders. The students chose the silhouette they considered healthy, ideal and referring to their current appearance. The unsatisfactory body size and shape corresponded with the difference of their perception of current size and the ideal size. Evaluation of food intake markers of healthy (fruits, vegetables) and of risk (sweeten drinks, meat fat, chicken skin and fast-food) food consumption frequency, skipping meals habits, eating profiles and alcohol consumption were performed. Anthropomorphic measures of weight and height was used to calculate the body mass index and to classified the weight status. The chi square test was used in the comparisons between the proportions and the test t student was used in comparison the average. Multiple logistic regression was used to estimate the association of dissatisfaction with body image and variables of alcohol consumption, adjusted for gender, age, economic class and weight condition. Results: he prevalence of unsatisfactory with own body image was of 75.2%, not having difference between genders (p=0.89). Among the unsatisfactory with own body image, it was observed a higher ethanol consumption per day (25.14 versus 13.37g/day; p<0.01) when compared to the satisfactory subjects. The unsatisfactory with own body image presented a direct association with the consumption of spirit drinks (ORaj: 2.26 IC95%: 1.03; 4.97) and with experimentation of alcoholic beverage (ORaj: 2.33 IC95%: 1.28; 4.24). There were no significant associations between body image dissatisfaction and eating habits investigated. Conclusion: The unsatisfied university student with own body image presented higher consumption of ethanol daily and higher prevalence consumption of spirit drinks. The unsatisfactory with own body image not presented a association with students eating habits.